Expiration date label knowledge and food waste reduction: a synthesis and critical evaluation of policy recommendations - János Szenderák; Dániel Fróna; Mónika Rákos (Environmental Challenges)
Expiration date labels are fundamental policy tools; however, the information presented on these labels is often misinterpreted, resulting in the discarding of otherwise edible food. The confusion surrounding expiration date labels leads to unnecessary food waste and increases the pressure on natural resources. This research reviewed consumer understanding of expiration date labels and synthesized the policy recommendations. We found that consumers frequently experienced confusion about expiration date labels, and their interpretation was affected by contextual factors. Knowledge and understanding of expiration date labels varied considerably, while the range of policy proposals was relatively narrow, suggesting a restricted policy space. Consumer education and information campaigns were among the most common policy recommendations, despite their modest efficiency in altering consumer behavior. Standardizing expiration date labels and altering their physical appearance may enhance the efficiency of information transfer; however, the individual risk perception of different products must be taken into account. However, the limited scope of policy proposals can significantly hinder the effectiveness of resource management policies. Therefore, understanding real-life consumer habits and waste behavior when designing product- and region-specific policy responses is essential for enhancing sustainability efforts. Finally, we propose a simplified framework for possible policy interventions.